Audiotactile interactions in temporal perception. - Occelli, V; Spence, C; Zampini, M (2011)
In the present review, we focus on how commonalities in the ontogenetic development of the auditory and tactile sensory systems may inform the interplay between these signals in the temporal domain. In particular, we describe the results of behavioral studies that have investigated temporal resolution (in temporal order, synchrony/asynchrony, and simultaneity judgment tasks), as well as temporal numerosity perception, and similarities in the perception of frequency across touch and hearing. The evidence reviewed here highlights features of audiotactile temporal perception that are distinctive from those seen for other pairings of sensory modalities. For instance, audiotactile interactions are characterized in certain tasks (e.g., temporal numerosity judgments) by a more balanced reciprocal influence than are other modality pairings. Moreover, relative spatial position plays a different role in the temporal order and temporal recalibration processes for audiotactile stimulus pairings than for other modality pairings. The effect exerted by both the spatial arrangement of stimuli and attention on temporal order judgments is described. Moreover, a number of audiotactile interactions occurring during sensory-motor synchronization are highlighted. We also look at the audiotactile perception of rhythm and how it may be affected by musical training. The differences emerging from this body of research highlight the need for more extensive investigation into audiotactile temporal interactions. We conclude with a brief overview of some of the key issues deserving of further research in this area.